Getting the Most out of the Research Experience - Brian Roberts (Sage, 2007)
While each research situation is different and no book can fully prepare the researcher for what they experience – this book provides a guide to what may be expected. Brian Roberts takes the researcher through the research process, answering the practical and subjective questions anyone will face: entering the field and finding the right research topic; emotional and identity issues of research; overcoming writing and research ′blocks′; getting your research into reports, articles, and books; reactions to research and how to handle experiences of rejection; and the questions every researcher should ask: What do I get from research, and what next? Loaded with advice on everything from organizing interpretations to coping with stress, this book is a must-read for students of all levels across the social sciences who are about to enter the research field.